Prevalence and Associated Predictors of Hypertension in Adult Patients with Thyroid Nodules at the Royal Commission Hospital, Kingdom of Saudi Arabia - Khair, Ahmed M; Ahmed, Mona A Sid; Alharbi, Faisal H; hassan, Soha; Elbadwi, Nusaiba M; Almutairi, Sami Naji; Musa, Imad R (Cardiology and Cardiovascular Medicine, 2023)
Background: Hypertension and thyroid nodules (TNs) are common medical problems that are increasing in prevalence globally. Hence, we conducted this study to assess the prevalence and associated predictors of hypertension in adult patients with TNs at the Royal Commission Hospital, Kingdom of Saudi Arabia (KSA). Methods: A retrospective study was conducted between 1 January 2015 and 31 December 2021. Patients with documented TNs based on the Thyroid Imaging Reporting and Data System (TI-RADS) were recruited to assess the prevalence and associated risk factors for hypertension. Result: Three hundred ninety-one patients with TNs were recruited for this study. The median (interquartile range, IQR) age was 46.00 (20.0) years, and 332 (84.9%) of the patients were females. The median (IQR) body mass index (BMI) was 30.26 (7.71) kg/m2. There was a high prevalence of hypertension (22.5%) in adult patients with TNs. In the univariate analysis, there were significant associations between diagnosed hypertension in patients with TNs and age, sex, diabetes mellitus (DM), bronchial asthma, triiodothyronine (FT3), total cholesterol and high-density lipoprotein (HDL). In the multivariate analysis, age (OR = 1.076 [95% CI 1.048 - 1.105]), sex (OR = 2.28 [95% CI 1.132 - 4.591]), DM (OR = 0.316 [95% CI 0.175 - 0.573]) and total cholesterol levels (OR = 0.820 [95% CI 0.694 - 0.969]) were significantly associated with hypertension. Conclusion: There is a high prevalence of hypertension in patients with TNs. Age, female sex, DM and elevated total cholesterol are significant predictors of hypertension in adult patients with TNs.